2019
DOI: 10.1016/j.mee.2019.110984
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the intermediate conductance states in RRAM devices for synaptic applications

Abstract: RRAM devices are promising candidates to implement artificial synaptic devices for their use in neuromorphic systems, due to their high number or reachable conductance levels.The capacitors used in this work (TiN/Ti/ HfO2/W) show resistive switching behavior and reachable intermediate conductance states. We can control the conductance states by applying voltage pulses to the top electrode. Different approaches to control the synaptic weight have been studied: applying pulses with different amplitudes changes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…When using voltage pulses, simulations demonstrated the final conductance value has a strong relationship with the pulse length [17]. We observed a higher number of pulses was required to reach the same final synaptic weight when applying voltage pulses, giving place to an accumulative process, although the potentiation characteristic obtained was not linear [9]. In order to check this behavior for current pulses, we applied three series of 50 pulses with different pulse lengths, from 1 µs to 50 µs, increasing the amplitude from 0 mA to 5.8 mA.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…When using voltage pulses, simulations demonstrated the final conductance value has a strong relationship with the pulse length [17]. We observed a higher number of pulses was required to reach the same final synaptic weight when applying voltage pulses, giving place to an accumulative process, although the potentiation characteristic obtained was not linear [9]. In order to check this behavior for current pulses, we applied three series of 50 pulses with different pulse lengths, from 1 µs to 50 µs, increasing the amplitude from 0 mA to 5.8 mA.…”
Section: Resultsmentioning
confidence: 78%
“…In a previous work, we studied the control of the conductance states in HfO 2 -based metal-insulator-metal (MIM) capacitors applying voltage pulses [9]. We obtained linear depression characteristics, but a non-linear potentiation characteristic due to the abrupt set transition.…”
Section: Introductionmentioning
confidence: 98%
“…The depression characteristic (the LRS to the HRS transition) cannot be controlled by varying the maximum negative current applied due to the abrupt LRS to HRS transition. However, the depression characteristic is the one better controlled by applying voltage instead of current signals to the sample [7].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we studied the control of the intermediate conductance states in hafnium oxide (HfO2) based metalinsulator-metal (MIM) capacitors, by applying voltage pulses [7]. In the case of the potentiation characteristic, we obtained a bad behavior due to the abrupt set characteristic.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous work [3] we show that TiN/Ti/ HfO2/W capacitors exhibit resistive switching behavior and that intermediate conductance states can be obtained by varying the voltage applied to the device (Voltage-control mode, VCM). We demonstrated that the conductance values vary near linearly when applying voltage depression pulses.…”
Section: Introductionmentioning
confidence: 92%